Sleep Disordered Breathing, Daytime Symptoms, and Functional Performance in Stable Heart Failure - Redeker, Nancy S. (Associated Professional Sleep Societies, LLC, 2010)
STUDY OBJECTIVES: To evaluate characteristics of sleep disordered breathing (SDB); clinical and demographic correlates of SDB; and the extent to which SDB explains functional performance and symptoms in stable heart failure patients receiving care in structured HF disease management programs. DESIGN: Cross-sectional, observational study. SETTING: Structured heart failure disease management programs. PARTICIPANTS: 170 stable chronic heart failure patients (mean age = 60.3 ± 16.8 years; n = 60 [35%] female; n = 50 [29%] African American; left ventricular ejection fraction mean = 32 ± 14.6). INTERVENTIONS: N/A MEASUREMENTS AND RESULTS: Full polysomnography was obtained for one night on participants in their homes. Participants completed the 6-minute walk, 3 days of actigraphy, MOS-SF 36, Epworth Sleepiness Scale, Pittsburgh Sleep Quality Index, Multi-Dimensional Assessment of Fatigue Scale, and the Centers for the Epidemiological Studies of Depression Scale. Fifty-one percent had significant SDB; Sixteen (9%) of the total sample had central sleep apnea. Severe SDB was associated with a 4-fold increase in the likelihood of poor self-reported physical function (OR = 4.15, 95%CI = 1.19–14.57) and CSA was associated with low levels of daytime mobility (OR = 4.09, 95%CI = 1.23–13.62) after controlling for clinical and demographic variables. There were no statistically significant relationships between SDB and daytime symptoms or self-reported sleep, despite poorer objective sleep quality in patients with SDB. CONCLUSIONS: Severe SDB is associated with poor physical function in patients with stable HF but not with daytime symptoms or self-reported sleep, despite poorer objective sleep quality in patients with SDB. CITATION: Redeker NS; Muench U; Zucker MJ; Walsleben J; Gilbert M; Freudenberger R; Chen M; Campbell D; Blank L; Berkowitz R; Adams L; Rapoport DM. Sleep disordered breathing, daytime symptoms, and functional performance in stable heart failure. SLEEP 2010;33(4):551-560.